Residual Marine Algae Biomass - An Important Raw Material for Obtaining a Soil Biostimulator-Regenerator (European Journal of Natural Sciences and Medicine, 2019)
This paper highlight a study regarding the valorification of residual marine algae biomass along Romanian Black Sea Coast, which recorded in the last summer period an accumulation of a large seaweed biomass quantities. The valorization of this waste was conceived as a result of theirs nutritional potential for improvind degraded soils of Dobrudja region, Romania and as complex capitalization of this biomass. It was establish the biotechnological process for the new biosolid nutrient composite obtaining. The parameter physical-chemical results of raw material used for biofertilizer obtaining, emphasized an increased organic charge compared with the inorganic compounds. Also, an increased value of total organic nitrogen and an optimum pH limits, was registered. Regarding the nutrients concentrations values, it could be noticed that the new biosolid fertilizer contains organic matter and valuable nutritive elements (N, P) could be contributed to the enhancement of the soil quality. The new biosolid biostimulator-regenerator obtained from natural residues bring a complex of nutrients for degraded soils by the presence of organic residual compounds, through the proteins, lipids, nutrients (nitrogen, phosphorus) and mineral salts content, necessary for plants nutrition and improvement of soils quality.